Source-specific perforated attenuators for use with pixelated spectroscopic X-ray detectors - Ryan, Daniel F; Peretz, Eliad; Christe, Steven D; Gregory, Kyle J; Kochergin, Vladimir; Zaynetdinov, Madrakhim; Fugaro, Andrew P; Kobhergin, Eugene (SPIE, 2021)
We outline progress in the development of novel perforated X-ray attenuators for fine-pitch (50{400 mm) spectro- scopic X-ray detectors composed of hundreds or thousands of pixels. Simple attenuators made of solid slabs of material drastically suppress the low energy signal which can reduce the scientific value of observations. By contrast, perforated attenuators can be designed to suit the shape and intensity of the expected incident spectrum, thus allowing a wider spectral range to be reliably measured. This is achieved by fabricating regions of different thicknesses on spatial scales smaller than the pixels and replicated over grids of hundreds or thousands of pixels. Perforated attenuators can enhance the scientific value of observations because they can enable multiple physical processes that dominate different regions of the X-ray spectrum to be observed simultaneously, e.g. lower energy thermal and higher energy non-thermal processes in solar flares. For this reason, a perforated attenuator will be own onboard the FOXSI-4 sounding rocket as part of a solar are campaign. In this paper we describe specific designs and fabrication methods and demonstrate the concept by measuring the transmission profiles of a number of prototypes. We conclude that such designs can be reliably produced with current fabrication techniques including microlithography and macroporous silicon technology, and can achieve transmission profiles desirable for solar are observations. Work described in this paper is the subject of pending patents.